Risk factors associated with peritoneal carcinomatosis of gastric cancer in staging laparoscopy: A systematic review and meta-analysis - Guan, Guangmin; Li, Zhemin; Wang, Qi; Ying, Xiangji; Shan, Fei; Li, Ziyu (Frontiers in Oncology, 2022)
Background: The optimal indication of staging laparoscopy in gastric cancer to detect peritoneal carcinomatosis is still a matter of debate. We performed this systematic review and meta-analysis to summarize the preoperative risk factors of peritoneal carcinomatosis to exploring the indications. Materials and methods: Systematic searches were conducted using Medline, Embase, and the Cochrane Library in December 2021. Based on calculating odds ratio (OR) of each factor, we quantified the association between several risk factors and peritoneal carcinomatosis such as clinical T/N stage, Borrmann type, tumor markers and so on, using meta-analysis with random-effects model. Results: 22 studies were obtained, all of them were case-control study except for one cohort study. T stage, N stage and cell differentiation were most widely studied, with OR values of 2.96 (95%CI:1.87-4.69), 1.22 (95%CI:0.86-1.73) and 1.91 (95%CI:1.42-2.56), respectively. Among all the factors, elevated CA125(OR=19.45, 95%CI:4.71.-80.30), Borrmann IV (OR=7.68, 95%CI:3.62-16.27), large tumor diameter (OR=5.12, 95%CI:2.55-10.31) had highest odds ratio. Particularly, CA125 had the best predictability for peritoneal carcinomatosis, but was only mentioned by 3 articles. Conclusions: There was a cognitive gap between awareness and importance for risk factors of peritoneal carcinomatosis. Besides commonly used clinical stage, it is necessary to include factors with high odds ratio such as Borrmann type, tumor diameter and tumor marker to build better predictive models for peritoneal carcinomatosis.